Socialization of "Be Brave to Speak,Be Brave to Create" as an Effort to Build Communication Skills and Self-Confidence of Vocational Students - Adnan Muhammad Husein; Annisa Galuh Nur Fitriani; Fadilah Ayu Novita Ramadhani; Fajar Wais Al Choiri; Naufal Rifqi Nugraha; Rahmalia Septiana; Yuliyanto Adi Firmansyah; Wahyuning Chumaeson (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Effective oral communication skills, especially public speaking, are essential capabilities that vocational high school (SMK) graduates must have to succeed in the increasingly competitive job market. However, observations at SMK Pandanaran Boyolali revealed that many students were experiencing high levels of communication anxiety and low self-confidence, mainly due to psychological barriers. To address this, a community service program was initiated with the title 'Berani Bicara, Berani Berkarya', with the aim of building students' self-assurance and verbal communication skills. The activity utilized a qualitative-observational approach, involving 35 students from grades X and XI.The program consisted of three main phases: a presentation on the importance of public speaking, screening of creative documentary videos to inspire motivation, and a hands-on practice session for speaking. Observations after the activity showed a significant increase in students’ enthusiasm and confidence. The participatory approach and the creation of a supportive environment proved effective in reducing speech anxiety. Overall, the initiative successfully encouraged students to step out of their comfort zones and provided them with practical experience crucial for their personal growth and future career preparedness.